A stochastic killing system for biological containment of Escherichia coli. - Klemm, P (1995)
Bacteria with a stochastic conditional lethal containment system have been constructed. The invertible switch promoter located upstream of the fimA gene from Escherichia coli was inserted as expression cassette in front of the lethal gef gene deleted of its own natural promoter. The resulting fusion was placed on a plasmid and transformed to E. coli. The phenotype connected with the presence of such a plasmid was to reduce the population growth rate with increasing significance as the cell growth rate was reduced. In very fast growing cells, there was no measurable effect on growth rate. When a culture of E. coli harboring the plasmid comprising the containment system is left as stationary cells in suspension without nutrients, viability drops exponentially over a period of several days, in contrast to the control cells, which maintain viability nearly unaffected during the same period of time. Similar results were obtained with a strain in which the killing cassette was inserted in the chromosome. In competition with noncontained cells during growth, the contained cells are always outcompeted. Stochastic killing obtained by the fim-gef fusion is at present relevant only as a containment approach for E. coli, but the model may be mimicked in other organisms by using species-specific stochastic expression systems.